Effects of the COVID-19 Pandemic on Children and Adolescents from the Perspective of Teachers - Senft, Birgit; Liebhauser, Astrid; Tremschnig, Ina; Ferijanz, Edith; Wladika, Wolfgang (Frontiers in Education, 2022)
The effects that the COVID-19 pandemic has had on children and adolescents are versatile and vast. reduced quality of life, emotional problems, social withdrawal, and symptoms of anxiety and depression up to suicidal ideations have been reported in numerous studies. They mainly use self-assessment, quite a few use parental assessments. The focus of this study are the challenges for teachers and students as well as observable behaviors and burdens of students from the perspective of teachers during the phase of distance learning because of the COVID-19 pandemic. The online study was conducted in Carinthia/Austria in March and April 2021. 1,281 teachers (29% response rate) from the 5th to the 13th grade participated. The significantly increased workload, the blurring of work and free time as well as the increased physical and mental demands are the largest challenges for the teachers. More than half of the students showed a significant drop in performance, reduced concentration ability and motivation to learn from the perspective of the teachers. Assumed is a critically increased media use. Next to social withdrawal, one can also perceive symptoms of anxiety, depression, or physical ailments. Because of the external assessment through teachers the results are not directly comparable with international studies. However, they do show to the same degree the urgency of preventive and secondary preventive resp. measurements as well as easily accessible possibilities for support for teachers and students. Teachers have a high sensitivity to peculiarities of students and are a valuable source of information.